Do state governments have the right to kill civilians to defeat international terrorism? Views from US, Israel and South Africa. Issue 2 (18th May 2020) - Shachat, Michael; Hong, Fang; Lin, Yijing; Desivilya, Helena Syna; Yassour-Borochowitz, Dalit; Akhurst, Jacqui; Leach, Mark M.; Malley-Morrison, Kathleen
Abstract : Purpose: This study aim to examine the themes of moral disengagement (MD) and engagement in reasoning regarding a putative governmental right to kill innocent civilians when fighting terrorism. Design/methodology/approach: In total, 147 participants from Israel, 101 from the USA and 80 from South Africa provided quantitative rating scale responses and qualitative explanations about such a putative right. Qualitative responses were coded for presence or absence of indices of MD and engagement. Findings: In ANOVAs by gender and country, men scored higher than women on rating scale scores indicating support for the right; there were no significant national differences on these scores. Chi-square analyses with the coded qualitative responses indicated more men than women gave morally disengaged responses, proportionately more South Africans than Israelis provided morally disengaged responses and proportionately more South Africans and Americans than Israelis provided morally engaged responses. Pearson correlation analyses indicated that MD was positively correlated with rating scale scores and moral engagement was negatively related to rating scale scores in all three countries. Research limitations/implications: Regarding limitations, it is difficult to know how the omission of qualitative explanations of rating scale responses by many participants influenced the statistical findings – or how to interpret the more restricted level of qualitative responses in Israel and South Africa as compared to the USA. Social implications: Programs designed to counteract MD have the potential for helping reduce support for war and its inhumanities across diverse nations. Originality/value: This is the first study on MD to compare American, Israeli and South African perspectives on the justifiability of human rights violations in the war on terror. The findings go beyond earlier studies in finding gender differences in MD that occurred across three very different nations in three very different parts of the world.